Phytoplankton communities provide insight into ecosystem functioning of the Agulhas Current system - Gibb, Ross-Lynne Alida (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Access restricted. Embargoed until 2025.
Keywords: Uncatalogued